ASSESSMENT OF CYTOKINE LEVEL IN BLOOD SERUM IN PREGNANT WOMEN WITH CHRONIC ARTERIAL HYPERTENSION IN THE FIRST TRIMESTER OF PREGNANCY - Лариса Дмитриевна Андосова; Анна Алексеевна Дмитриева; Людмила Васильевна Боровкова; Светлана Олеговна Колобова; Ксения Андреевна Шахова; Юлия Рудольфовна Тихомирова; Александр Алексеевич Туличев; Людмила Александровна Чичкова (Мать и дитя в Кузбассе, 2024)
Purpose of the study – to assess the content of cytokines IL-8, IL-1b and MCP-1 in the first trimester of pregnancy in women with chronic arterial hypertension.